THE SCHOOL STRATEGY IN STRENGTHENING THE CHARACTER OF NATIONALISM IN STUDENTS OF SDN 8 PENA NA'E BIMA CITY - Syudirman; Nur Istaqam (Universitas Islam Negeri Mataram, 2024)
This research aims to describe the school's strategy for improving the nationalist character of students at SDN 8 Pena Na'e, Bima City, and the supporting factors for increasing the nationalist character of students at SDN 8 Pena Na'e, Bima City. This research uses a descriptive qualitative approach. This research was carried out at SDN 8 Pena Na'e, Bima City. Data sources from teachers and students. The data collection techniques used were observation, interviews, and documentation. To ensure the validity of the data, triangulation techniques were used. Based on the research results, it was found that the school's strategy for improving students' nationalistic character is: (1) The school involves its students in taking part in the flag ceremony every Monday morning, (2) The school involved students in a cultural parade wearing traditional regional clothing, (3) involvement of students in following beautiful walks, (4) involvement of students in Lenggo cultural dances. It is hoped that this article will contribute to developing a theoretical framework and practical strategies for developing knowledge in Indonesia